Rapid Knowledge Mobilization and Continuing Professional Development: Educational Responses to COVID-19. Issue 1 (2nd April 2022) - Rowland, Paula; Tavares, Walter; Lowe, Mandy; Tripp, Tim; Richardson, Juanita; Anderson, Melanie; Oja, Lori Anne; Paton, Morag; Wiljer, David; Woods, Nicole; Ng, Stella
Abstract : Introduction: The field of Continuing Professional Development (CPD) has a role to play in supporting health care professionals as they respond to the COVID-19 pandemic. However, the evolving science of COVID-19, the need for quick action, and the disruption of conventional knowledge networks pose challenges to existing CPD practices. To meet these emergent and rapidly evolving needs, what is required is an approach to CPD that draws insights from the domain of knowledge mobilization (KMb). Methods: This short report describes a research protocol for exploring rapid KMb responses to COVID-19 at one Canadian academic teaching hospital. The proposed research will proceed as a case study using a mixed methods design collecting quantitative (surveys and Web site use metrics) and qualitative data (interviews) from individuals involved in developing, using, and supporting the KMb resources. Analysis will proceed in two phases: descriptive analysis of data to share insights and integrative analysis of data to build theory. Results: Results from this study will inform the immediate KMb and CPD contribution to the COVID-19 response. Discussion: Findings from this study will also make a broader contribution to the field of CPD, theoretically informing intersections between KMb and CPD and therefore contributing to an integrated science of CPD.